2009
DOI: 10.1002/ana.21591
|View full text |Cite
|
Sign up to set email alerts
|

Clinical‐neuroimaging characteristics of dysexecutive mild cognitive impairment

Abstract: Objective-Subgroups of mild cognitive impairment (MCI) have been proposed, but few studies have investigated the non-amnestic, single-domain subgroup of MCI. The goal of the study was to compare clinical and neuroimaging characteristics of two single domain MCI subgroups: amnestic MCI (aMCI) and dysexecutive MCI (dMCI).Methods-We compared the cognitive, functional, behavioral and brain imaging characteristics of patients with aMCI (n=26), dMCI (n=32) and age-and education-matched controls (n=36) using analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
85
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 44 publications
10
85
0
8
Order By: Relevance
“…Thus, the literature suggests that individuals with MCI have WM deficits that are evident irrespective of the sensory modality of the information and the MCI subtype. The underlying mechanisms for these deficits remain uncertain, but pathological changes in the brain regions that subserve WM, such as frontal lobe atrophy [20,21] and dysfunction [22,23], likely contribute to these deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the literature suggests that individuals with MCI have WM deficits that are evident irrespective of the sensory modality of the information and the MCI subtype. The underlying mechanisms for these deficits remain uncertain, but pathological changes in the brain regions that subserve WM, such as frontal lobe atrophy [20,21] and dysfunction [22,23], likely contribute to these deficits.…”
Section: Introductionmentioning
confidence: 99%
“…A recent amyloid imaging study with Pittsburgh compound B revealed no differences between aMCI and naMCI [12]. In MRI studies, mesial, inferior temporal, right inferior parietal and posterior cingulate cortex atrophy were more pronounced in aMCI than naMCI [13,14,15,16]. White matter loss in periventricular areas as well as in the frontal, parietal, temporal and posterior cingulate cortex and the splenium of corpus callosum were also more common in aMCI [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Nonamnestic MCI cases displayed less severe gray matter and white matter loss in the mesial temporal lobe [14,16,21], diffuse white matter changes in other cortical areas [18] and a greater proportion of cortical infarcts compared to aMCI [13]. In contrast to aMCI cases that display mesial temporal lobe, inferior parietal and posterior cingulate cortex atrophy, dysexecutive MCI cases have more pronounced left frontal lobe damage [22]. …”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the different non-amnestic single-domain MCI subgroups (e.g. dysexecutive, language, visuospatial) will have distinct clinical features and different risks for converting to dementia [7,8] . It is, therefore, important to subdivide single-domain non-amnestic MCI groups to improve clinical differentiation.…”
mentioning
confidence: 99%